Digital Ekonomi dan Pemberdayaan Pengelolaan Keuangan Guna Meningkatkan Pelayanan dan Kemampuan Manajerial pada SMK Muhammadiyah 3 Pekanbaru - Winarso, Doni; Edo Arribe; Muhammad Ahyaruddin (LPPM UMRI, 2023)
Sekolah Menengah Kejuruan (SMK) 3 Pekanbaru city is an educational institution under the Amal Usaha Muhammadi(AUM) which equips its students with vocational training and Al-Islam Kemuhammadiyahan values. The problems faced by partners are 1) Principals' difficulties in controlling budget use because financial management is still done manually so it can impact the decision-making process 2) Services to students are not yet supported by adequate technology and information systems. From several problems that exist with partners, So service is prioritized on financial issues. The solutions offered to partners in overcoming several problems include 1) Education and empowerment of school financial management in supporting financial services, 2) Digital economy to improve services and make it easier for managers to make policies. The main output of this service is increasing the management and financial service capabilities of partners and assisting managers, especially school principals, in making decisions based on real financial data based on appropriate technology in the form of a school financial management information system at SMK Muhammadiyah 3 Pekanbaru